2012
DOI: 10.1002/chem.201201472
|View full text |Cite
|
Sign up to set email alerts
|

Water Oxidation with Molecularly Defined Iridium Complexes: Insights into Homogeneous versus Heterogeneous Catalysis

Abstract: Molecularly defined Ir complexes and different samples of supported IrO(2) nanoparticles have been tested and compared in the catalytic water oxidation with cerium ammonium nitrate (CAN) as the oxidant. By comparing the activity of nano-scaled supported IrO(2) particles to the one of organometallic complexes it is shown that the overall activity of the homogeneous Ir precursors is defined by both the formation of the homogeneous active species and its conversion to Ir(IV)-oxo nanoparticles. In the first phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 73 publications
1
61
0
1
Order By: Relevance
“…Junge et al reported that a significant amount of the Ir IV species (28.5-82 % IrO 2 of Ir species) was formed for homogeneous iridium catalysts after water oxidation reaction at the high CAN concentration of 170 mm. [6] Our results suggest that no iridium oxide nanoparticles form within the first seven reactions and that iridium complexes strongly coordinate with the pore surface of BPy-PMO. The slight differences in EXAFS results are due to the decomposition of the Cp* ligand and the change in the coordination environment of iridium.…”
mentioning
confidence: 94%
“…Junge et al reported that a significant amount of the Ir IV species (28.5-82 % IrO 2 of Ir species) was formed for homogeneous iridium catalysts after water oxidation reaction at the high CAN concentration of 170 mm. [6] Our results suggest that no iridium oxide nanoparticles form within the first seven reactions and that iridium complexes strongly coordinate with the pore surface of BPy-PMO. The slight differences in EXAFS results are due to the decomposition of the Cp* ligand and the change in the coordination environment of iridium.…”
mentioning
confidence: 94%
“…from experiments using a quartz microbalance as a probe and from catalyst immobilization. [35][36][37] Direct comparison of results across the broad range of mechanistic investigations reported in literature is difficult due to varying reaction conditions including the use or absence of organic co-solvents and buffered or unbuffered aqueous conditions. Following our initial discovery of triazolylidene iridium complexes as potent water oxidation catalysts, we engaged in careful ligand modification in an attempt to improve catalyst performance and to expand our understanding of oxidation mechanisms with application to a broad variety of fuel producing photosystems.…”
Section: Introductionmentioning
confidence: 99%
“…19 Moreover, kinetic and mechanistic studies have provide increasingly compelling evidence that some complexes are precursors for homogeneous rather than heterogeneous [20][21][22] water oxidation catalysts and that the oxidation therefore occurs at an iridium center that is in a well-defined environment. 19,[23][24][25][26][27][28] This environment has remained elusive up to now despite various efforts to trap and isolate catalytically competent species. [29][30][31][32] In particular iridium cyclopentadienyl complexes [Ir(Cp*)(L,L)X] + containing a chelating N,N-, C,N-, or C,Cbidentate ligand motive afforded high catalytic activity (Cp* = = C 5 Me 5 -).…”
Section: Introductionmentioning
confidence: 99%